Homogeneous reporter system enables quantitative functional assessment of multiple transcription factors - Romanov, Sergei; Medvedev, Alexander; Gambarian, Maria; Poltoratskaya, Natalia; Moeser, Matt; Medvedeva, Liubov; Gambarian, Mikhail; Diatchenko, Luda; Makarov, Sergei (Nature methods, 2008)
We developed a high-content reporter system that allows quantitative assessment of activities of multiple transcription factors (TFs) in a eukaryotic cell. The system comprises a library of reporter constructs that are evaluated according to their transcription rates. All reporters produce essentially identical messages that are subjected to 'processing', which generates a spectrum of distinguishable fragments that are analyzed quantitatively. The homogeneity of the reporter library afforded inherently uniform detection conditions for all reporters and provided repeatability, accuracy and robustness of assessment. We showed that this technology can be used to identify pathways transmitting cell responses to inducers, and that the profile of TF activities generated using this system represents a stable and sustained cell signature that clearly distinguishes different cell types and pathological conditions. This technology provides a framework for functional characterization of signal transduction networks through profiling activities of multiple TFs.